Islamic social finance in addressing poverty and economic growth: using structural equation modelling - Muhammad, Tijjani; Al-Shaghdari, Fahd Mohammed Obad (USIM Press, 2023)
Islamic social finance is one of the sources of funds in the Islamic economic system. It refers to voluntary philanthropic activities that have a unique presence in Islam. Islamic law is the first to define and regulate Zakat and Waqfs as civil society institutions. Currently, microcredit and microfinance programs are unsuccessful in reducing poverty and income inequality in Northern Nigeria. Islamic social finance institutions are promoting programs such as offering free education, scholarships, free medical care, and orphanage activities around the globe. However, in Nigeria, such Islamic social finance is currently growing slowly. This paper investigates people's perception of reducing poverty and promoting sustainable economic development in Northern Nigeria. The study employed random sampling using Structural Equation Modeling (SEM) for the analysis. Findings indicate the relationship between Waqf and sustainable economic development and Zakat and sustainable economic development as a direct effect. The findings indicated that Waqf and Zakat significantly reduce poverty, and Poverty reduction promotes and enhances sustainable economic development in Northern Nigeria. The study further suggests and recommends that the Northern states, where the majority of the citizens are Muslim, deserve serious consideration for developing Zakat and Waqf institutions in the region to assist in reducing the vulnerable group in society.